ANALISIS BELANJA DAERAH DI KABUPATEN KOTAWARINGIN BARAT - Septa Soraida (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to analyze spending on the West Kotawaringin district government in 2018-2020. The results of this study indicate that the year of growth in regional expenditures increased in 2019 and decreased in 2020. The Expenditure Conformity Analysis shows that in 2018-2020 the West Kotawaringin district government tends to have more operational expenditures compared to capital expenditures and the analysis of the level of efficiency of expenditures shows an average an average of 93.33% means that the level of conformity between the budget and realization is in the efficient criteria.